Influence of heat-source temperature on convection-based tilt sensor output - Yang-hong Zheng; Shi-liu Peng (2012 International Conference on Measurement, Information and Control, 2012)
According to the sensitive mechanism of convection-based tilt sensor, temperature field plays a key role in the sensing tilt. The tilt sensor output has one to one correspondence with the temperature field, which is variety with heat-source temperature. Using ANSYS, temperature flow fields are simulated by variety heat-source temperatures in a two dimension hermetic chamber, the differences of temperature between hotwires are obtained, the outputs based on these are calculated, also compared with measured values. From the results the output relation with the heat-source temperature is given qualitatively1. figurate; qualitative, through this relation the output of sensor can be improved, meanwhile output drifted with heat-source temperature can be decreased by provided circuit.